Conformal radiotherapy plans for palliative bone metastasis - comparison of dosimetric parameters - Gupta, Naina; Dr. Pavan Kumar; Kumar, Piyush; Navitha, S.; Mehta, Ankita; Chauhan, Arvind (International Journal of Medical Research and Review, 2020)
Background:Palliative radiotherapy offers significant relief in the huge physical distress of patients with bony metastasis. The enormous potential of conformal techniques has not been tested in palliative settings. However,the increasing life span of patients with metastatic disease demands to optimize the radiotherapy techniques to provide maximal durable symptomatic relief. Despitean increase in the utilization of the 3DCRT technique for palliative bony metastasis, the optimal beam arrangement remains unknown. Materials and Methods:Ten patients of vertebral bony metastasis were retrospectively selected and four virtual 3DCRT plans were generated for each patient. The field approaches were a single field, two fields, three fields and five field approaches. For PTV, D90, D50, Dmean, Conformity index (CI) were evaluated.Dmean was evaluated for the esophagus, bowel, kidneys, and combined lungs. Dose-volume histograms were computed for the various treatment plans and compared. Statistical analysis was done by ANOVA test. Results:A total of forty radiotherapy plans were generated. PTV parameters were significantly better with two field plans over one field plans in terms of D90 (p= 0.002), D50 (p= 0.02), Dmean(p=0.0009). Dmeanwassignificantly better with three field approach compared to two field approach (p=0.0006). The Dmeanwas significantly increased for organs at risk in two fields and three field plans.Five field approach did not showan advantage in terms of dosimetry of PTV but there was a significant rise in the dose to Organs at risk (OAR’s). Conclusion:The three field plans showed better dose distribution to the PTV with an acceptable increase in the dose to OAR’s.